An Isocratic Method for Quantification of Valproic Acid and Its Related Impurities Using Ion Pair Reagent by Ultraperformance Liquid Chromatography. (17th December 2012) - Thakkar, Rakshit; Saravaia, Hitesh; Ambasana, Mrunal; Patel, Madhavi; Shah, Anamik
Abstract : A selective ultraperformance liquid chromatographic (UPLC) method for the quantification of valproic acid and its known related impurities using ion pair reagent has been developed. The method includes reversed-phase Acquity HSS T3 column with 100 mm × 2.1 mm i.d. and 1.7  μ particle size. The mobile phase consists of acetonitrile, 5 mM 1-hexanesulphonic acid sodium salt, flow rate is 0.6 mL/min, and UV detection is performed at 215 nm. A system suitability test (SST) was developed to govern the quality of the separation. The developed method has been validated further with respect to linearity, accuracy, precision, selectivity, LOD, LOQ, and Robustness.